FIRE EFECT ON THE SEASONAL FOREST STRUCTURE IN THE CERRADO BIOME - Pereira, Iokanam Sales; Calil, Francine Neves; Martins, Thalles Oliveira; Silva-Neto, Carlos de Melo e; Borges, Jéssyca; Venturoli, Fábio; Oliveira, Lucas Henrique; Barbosa, Pedro Vilela G.; Xavier, Ana Carolina Freitas; Gonçalves, Bruno Bastos (Floresta, 2017)
There are few studies on the effects of fire on the seasonal semideciduous forest of the Cerrado region. This study aimed to assess the effect of fire on Semideciduous forest fragments located in the Altamiro Moura Pacheco State Park (AMPSP). The study area is located in the central state of Goiás. A total of 10 plots (50 x 20 m; 1,000 m2) were drawn in the remaining forests seeking to portray two areas: area which underwent forest fire (burned area; B) and unburned area (unburned; UB). A total of 771 individuals with DBH (≥ 5 cm) were identified. A total of 303 individuals were recorded in the burned area (B), comprising 28 families, 41 genera and 47 species, while the unburned area (UB) had 468 individuals comprising 25 families, 43 genera and 50 species. The species Anadenanthera colubrina (Vell.) Brenan, Emmotum nitens (Benth.), Zanthoxylum rhoifolium Lam, Tapirira guianensis Aubl., Myracrodruon urundeuva Allemão and Luehea candicans Mart. had the highest Importance Value Index (IVI) values and occur in both areas. The percentage of dead trees differed between the areas, where the burned area had a mortality of 12.69% and the unburned area of 7.29% in regards to the number of individuals. Density per plot was the only parameter that differed between the areas, where the burned area (B) had the lowest values. The fire affected all diameter classes, demonstrating the fragility of this vegetation type in regards to fire. The fire had a greater effect on trees in the smaller diameter classes, reducing the frequency of individuals in the burned area and changing height distribution, which may have favored the establishment of lianas and invasive species.